Breeding characteristics of Romanov sheep depending on polymorphism of growth hormone gene - Marina V. Abramova; Anna V. Ilina; Maria S. Barysheva; Julia I. Malina; Evgeniy G. Evdokimov (RUDN Journal of Agronomy and Animal Industries, 2022)
The search for new markers of high productivity of sheep and the introduction of evaluation and selection methods for these indicators is an urgent direction in breeding of Russian sheep. The material for the research was the results of assessment of exterior, live weight of Romanov sheep. Genetic studies were carried out using tissue samples (ear plucking). Polymorphism of growth hormone gene in Romanov sheep was evaluated by restriction fragment length polymorphism analysis and polymerase chain reaction. Evaluation of polymorphism of growth hormone gene in the population of Romanov sheep showed the presence of three allelic variants - AA, AB and BB, with a frequency of 0.24, 0.63 and 0.14, respectively. The statistically significant difference between the indicators of live weight in animals with genotypes GHAB and GHAA, GHAB and GHBB was: at birth 210 g and 140 g (P 0.95), respectively; at weaning 350 g and 1260 g (P 0.95), respectively. The phenotypic variability of live weight was the highest at birth and at weaning and amounted to 31.732.5 % for all genotypes. Animals with genotypes GHAA and GHAB outperformed their peers with genotype GHBB in dimensions of rump width in tuber coxae, rump width in tuber trochanterica, chest width, chest circumference, and therefore, had a wide body. When studying the phenotypic and genetic correlations of measurements of exterior and live weight at the age of 12 months, a reliable positive relationship was established with height at withers height (rP = +0.13*; rG = +0.02), rump height (rP = +0.14**; rG = +0.03), rump length (rP = +0.14**; rG = +0.02). The new knowledge gained about polymorphism of GH gene and its relationship with productive traits of Romanov sheep will allow for in-depth evaluation, targeted selection and selection of individuals with desirable genotypes.